DIVISION II: COMMISSION 10: SOLAR ACTIVITY. (13th August 2015) - van Driel-Gesztelyi, Lidia; Scrijver, Karel J.; Klimchuk, James A.; Charbonneau, Paul; Fletcher, Lyndsay; Hasan, S. Sirajul; Hudson, Hugh S.; Kusano, Kanya; Mandrini, Cristina H.; Peter, Hardi; Vršnak, Bojan; Yan, Yihua
Abstract : The Business Meeting of Commission 10 was held as part of the Business Meeting of Division II (Sun and Heliosphere), chaired by Valentin Martínez-Pillet, the President of the Division. The President of Commission 10 (C10; Solar activity), Lidia van Driel-Gesztelyi, took the chair for the business meeting of C10. She summarised the activities of C10 over the triennium and the election of the incoming OC.